POTENSI DAN PERANAN ZAKAT DALAM MENGENTASKAN KEMISKINAN DI KOTA MEDAN - Amalia Amalia; Kasyful Mahalli (Ekonomi dan Keuangan, 2012)
Zakat is one of the alternative solutions to reduce poverty. the results of field studies indicate that the benefits of Zakat is distributed fairly good, but not optimal. although the year-over-year increase zakat but its realization is still less than the potential of the existing zakat. This research was conducted aimed to determine the potential level of relationship and influence the role of zakat to the poor in the city of Medan The method used in this study is the method of Spearman Rank correlation analysis. Data was collected by interview and questionnaires were distributed to District 10 of 21 district in the city of Medan with a total sample of 100 people.Once the data is collected, the authors analyze and interpret resulting conclusions. From the research it can be concluded that most people agree the Medan distribution and utilization of zakat, especially in the form of loans and capital are Qadrul Hasan and accompanied the training and skills provided to increase business progress.